If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(3x+2)=2(3x-5)
We move all terms to the left:
3(3x+2)-(2(3x-5))=0
We multiply parentheses
9x-(2(3x-5))+6=0
We calculate terms in parentheses: -(2(3x-5)), so:We get rid of parentheses
2(3x-5)
We multiply parentheses
6x-10
Back to the equation:
-(6x-10)
9x-6x+10+6=0
We add all the numbers together, and all the variables
3x+16=0
We move all terms containing x to the left, all other terms to the right
3x=-16
x=-16/3
x=-5+1/3
| -11d+14=-12d | | X^3-7x^2-49x+55=0 | | 19s–17s=-8 | | 4(r+3)=20 | | -14s-8s=-18 | | (√8-p)-(√p+5)=1 | | x+7=2x−2 | | G=8/7(p-5) | | x+7=2x−2x+7=2x−2 | | 0.125(3y+2)=0.25(2y+0.5)+0.5 | | 3(x+2)=4+2(x-1) | | 2(9y-1)=99-21 | | 8=(14/27)x | | -4x+3x=-8+25x | | 0.125(3y+2)=1/4(2y+0.5)+1/2 | | x+10/5=-9 | | 7(x+4)+7(x+4)=70 | | x-3/4=-1 | | 1/8(x+16)+1/4(x+4)=x-8 | | (10y-9)(3y+7)=0 | | -6(7x-6)=-42x-36 | | (y-50)=180 | | 8-3x=-x | | 6x2-x=2 | | y=2/3(0)-5/6 | | 2/3x+6=1/2x+x1/4 | | (3m-3)/5=7/10 | | (-4+5x)/(-8)=3 | | x/11-9=-3 | | 17.5x-7.5=27.5 | | 2(x^2)-3x-119=0 | | (x+1)^2+25=0 |